Body roll in simulated freestyle swimming - Lee, J.; Mellifont, R.; Winstanley, J.; Burkett, B. (International Journal of Sports Medicine, 2008)
This study analysed the timing and sequence of body roll relative to the propulsive phase of eleven elite freestyle swimmers on a custom built swim bench. Three dimensional kinematic data of the head, chest, and hips was collected and the effect of sex and breathing analysed using a linear mixed modelling approach. For the breathing stroke, there was a similar timing between males and females, with the head roll occurring at 30 % and 28 %, respectively, the chest at 42 % and 43 %, and the hips at 43 % and 40 % of the propulsive phase. Differences in timing for the nonbreathing stroke were observed between the sexes, with male hip roll occurring much earlier than females. Female hip and chest roll occurred almost simultaneously in the nonbreathing stroke. The sequence of movement for the non-breathing armstrokes was the same for both sexes (hip, chest, head). A significant difference in timing and sequence pattern was found for the breathing stroke with the head preceding the movement of the hips and chest for both males and females. Maximal body roll angles for the chest and hips showed variations between gender and stroke type. Distinct patterns of timing and sequence of body roll in simulated 100-m freestyle swimming were observed.